2000
DOI: 10.4141/a99-055
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding canola screenings on apparent digestibility, growth performance and carcass characteristics of feedlot lambs

Abstract: Effects of feeding canola screenings on apparent digestibility, growth performance and carcass characteristics of feedlot lambs. Can. J. Anim. Sci. 80: 355-362. Commercial coarse canola screenings (CS) were substituted for barley grain, and the resulting experimental diets (0, 20, 45, 70 and 95% CS, were evaluated in feedlot lambs, while the 0, 45 and 95% CS diets were evaluated in a digestibility study using Romanov × Suffolk lambs. The CS comprised 60% canola (as whole, broken and immature seeds), 25% weed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
2
0
0
Order By: Relevance
“…Also, BCPO caused a linear increase in the proportion of C20:5n-3. The current observation is consistent with those of Stanford et al [ 54 ] who observed that increasing the level of canola screening in diets reduced the concentration of C14:0, C16:0, C16:1n-7, C18:0 and total SFA and enhanced that of C18:1n-9, C18:3n-3, total MUFA and PUFA in perirenal adipose tissue in lambs. In contrast, dietary rapeseed oil, linseed oil or hydrogenated rapeseed oil did not alter the fatty acid composition of perirenal adipose tissues in lambs [ 55 ].…”
Section: Discussionsupporting
confidence: 93%
“…Also, BCPO caused a linear increase in the proportion of C20:5n-3. The current observation is consistent with those of Stanford et al [ 54 ] who observed that increasing the level of canola screening in diets reduced the concentration of C14:0, C16:0, C16:1n-7, C18:0 and total SFA and enhanced that of C18:1n-9, C18:3n-3, total MUFA and PUFA in perirenal adipose tissue in lambs. In contrast, dietary rapeseed oil, linseed oil or hydrogenated rapeseed oil did not alter the fatty acid composition of perirenal adipose tissues in lambs [ 55 ].…”
Section: Discussionsupporting
confidence: 93%
“…Overall growth performance of these lambs was at least equal to previous reports for early-weaned lambs individually fed highconcentrate diets (Stanford et al 2000). Feed intake by lambs fed the RRC diet was reduced (P < 0.05) compared to the COM1 and COM2 diets, but intake did not differ between lambs fed RRC and PAR.…”
Section: Growth Performancesupporting
confidence: 66%